The effect of an 8% cocoa bean extract gel on the healing of alveolar osteitis following tooth extraction in Wistar rats - I. Isnandar; Olivia Avriyanti Hanafiah; Muhammad Fauzan Lubis; Lokot Donna Lubis; Adzimatinur Pratiwi; Yeheskiel Satria Yoga Erlangga (Dental Journal (Majalah Kedokteran Gigi), 2022)
Background: Alveolar osteitis is a well-known complication that occurs following a tooth extraction when the clot within the socket breaks down too early, causing increased localised inflammation and extreme pain. Alveolar osteitis delays the wound healing process of the socket. The polyphenols in the cocoa bean (Theobroma cacao L.) can stimulate the wound healing process. Purpose: The aim of this study was to analyse the effect of an 8% cocoa bean extract gel on the healing of alveolar osteitis following a tooth extraction. Methods: This study is an in vivo experiment with a posttest-only control group design. Thirty-six male Wistar rats were divided into three groups: a negative control, positive control and an 8% cocoa bean extract gel. A tooth extraction was performed on the mandibular incisor, and alveolar osteitis was induced by the application of adrenaline using a paper point on the socket. On the 3rd, 7th and 14th days, the clinical wound size of the extraction socket was measured, and the rats were sacrificed to observe the number of macrophages, fibroblasts and osteoblasts microscopically. A two-way analysis of variance test and post hoc least significant difference test were used to analyse the data (p < 0.05). Results: The data analysis showed a significant difference in the clinical wound size of the extraction socket and the number of macrophages, fibroblasts and osteoblasts between the 8% cocoa bean extract gel and the control groups (p = 0.000). Conclusion: An 8% cocoa bean extract gel stimulates the healing of alveolar osteitis following tooth extraction in Wistar rats.